A Analisis Unsur Seksualitas dalam h’iem pada Masyarakat Kecamatan Kuta Makmur Kabupaten Aceh Utara - Misbahul Munir; Safriandi; Ririn Rahayu (Global Action and Education for Society, 2026)
This study aims to describe the elements of sexuality biological aspects in acehnese h'iem in the Kuta Makmur District community, North Aceh Regency. The approach used in this study is qualitative with a descriptive research type. The data in this study are h'iem obtained from the Kuta Makmur District community, North Aceh Regency. The data source for this study is the Kuta Makmur District community, North Aceh Regency, who master h'iem. The data collection techniques used are interviews, recording and note-taking. The stages of data analysis carried out are data reduction, data presentation, and drawing conclusions. The results show that of the 8 h'iem data found in the Kuta Makmur District community, North Aceh Regency, contain elements of sexuality depicted in h'iem through the choice of metaphorical and ambiguous diction, and are often associated with body organs and sexual activity. However, the meaning tends to be non-sexual, symbolic or humorous. The elements of sexuality found are biological elements.